Specification for Tunnelling Fourth edition (Emerald Publishing, 2024)
The ebook edition of this title is Open Access and freely available to read online. Specification for Tunnelling, Fourth edition is a standard industry document for tunnelling contracts and forms the basis of tunnelling specifications for projects throughout the world. It reflects current industry best practice and considers technological advancements over the last ten years. It also investigates a range of new topics. Since the publication of the third edition in 2010, the British tunnelling industry has completed several major projects both domestic and abroad. This updated fourth edition captures the many advances made in the field of tunnelling and the lessons learned on these projects through a comprehensive review of all content by subject matter experts. The importance of sustainability and the increased market share of low CO2e materials have been reflected by removal of prescriptive requirements and a strong emphasis on performance-based specification. All references to codes, standards and other design documents have been comprehensively updated. Drafted by an expert editorial committee and supported by multiple rounds of industry-wide peer reviews, the Specification for Tunnelling in its fourth edition will continue to be the de facto standard reference work for tunnelling in the UK and worldwide.
English
Keywords: Building construction & materials; Civil engineering, surveying & building; Construction & engineering law